Efficacy and Resistance of Afatinib in Chinese Non-Small Cell Lung Cancer Patients With HER2 Alterations: A Multicenter Retrospective Study - Song, Zhengbo; Lv, Dongqing; Chen, Shiqing; Huang, Jianhui; Wang, Liping; Xu, Shuguang; Chen, Huafei; Wang, Guoqiang; Lin, Quan (Frontiers in Oncology, 2021)
Background: Non-small cell lung cancer patients (NSCLC) with HER2 mutations and amplification may benefit from HER2-targeted therapy, including afatinib. However, the data regarding the clinical activity of afatinib in Chinese patients with NSCLC harboringHER2 alterations are limited. Patients and methods: We retrospectively included metastatic NSCLC patients harboringHER2 alterations who treated with afatinib. The clinical outcomes included overall response rate (ORR), progression-free survival (PFS) and overall survival (OS). The genomic profiling data after progression on afatinib were analyzed. Results: We included 54 patients harboring HER2 mutations and 12 patients harboring HER2 amplification. The ORR was 24% (95% CI, 16-36%), the median PFS was 3.3 months (95% CI, 2.2-4.4), and the median OS was 13.9 months (95% CI, 11.4-16.5). Patients with HER2 exon 20 mutations had numerically worse ORR (17% vs 42%), shorter PFS (2.6 vs 5.8 months, HR, 2.5; 95% CI, 1.2-5.5; P = 0.015) and OS (12.9 vs 33.3 months, HR, 4.4; 95% CI, 1.3-14.8; P = 0.009) than patients with other mutations.ForHER2-amplified patients, the ORR was 33% (95% CI, 14-61%), the median PFS was 3.3 months (95% CI, 2.6-4.0), and the median OS was 13.4months (95% CI, 0-27.6). The most frequently mutated genes in afatinib-resistant patients were TP53 (44%), and EGFR (33%). Three afatinib-resistant patients harbored secondary HER2 alterations. Conclusions: Our results suggest that afatinib has a promising anti-tumor activity in patients with NSCLC harboring HER2alterations. To our knowledge, this is the largest retrospective study about the clinical activity of afatinib in NSCLC patients with HER2 alterations.